2017
DOI: 10.3389/fneur.2017.00682
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Emotional Mirroring in Parkinson’s Disease—A Study on Brain Activation during Processing of Facial Expressions

Abstract: BackgroundAffective dysfunctions are common in patients with Parkinson’s disease, but the underlying neurobiological deviations have rarely been examined. Parkinson’s disease is characterized by a loss of dopamine neurons in the substantia nigra resulting in impairment of motor and non-motor basal ganglia-cortical loops. Concerning emotional deficits, some studies provide evidence for altered brain processing in limbic- and lateral-orbitofrontal gating loops. In a second line of evidence, human premotor and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 84 publications
2
16
0
4
Order By: Relevance
“…Emotion disturbance is a common non-motor symptom in PD patients, presenting as apathy, fatigue, anxiety, and depression (Li et al, 2017;Shen et al, 2018). Previous studies indicated that the emotional processing circuits were disrupted in PD patients (Pohl et al, 2017;Bell et al, 2019). In this study, HAMA and HAMD score were significantly higher in LOPD than those in HCo, while there was no significant difference between EOPD and HCy.…”
Section: Eopd With More Widespread Dysfunction In Emotional Processinmentioning
confidence: 39%
“…Emotion disturbance is a common non-motor symptom in PD patients, presenting as apathy, fatigue, anxiety, and depression (Li et al, 2017;Shen et al, 2018). Previous studies indicated that the emotional processing circuits were disrupted in PD patients (Pohl et al, 2017;Bell et al, 2019). In this study, HAMA and HAMD score were significantly higher in LOPD than those in HCo, while there was no significant difference between EOPD and HCy.…”
Section: Eopd With More Widespread Dysfunction In Emotional Processinmentioning
confidence: 39%
“…Neuropsychological studies (Jacobs, Shuren, Bowers, & Heilman, ; Livingstone, Vezer, McGarry, Lang, & Russo, ; Marneweck, Palermo, & Hammond, ; Ricciardi et al, ), similar to the already cited study of Pohl et al (), have also reported the existence of a significant relationship between voluntary control of facial muscles and emotion recognition deficits in PD patients, an interesting finding at the light of the embodied cognition framework. If the MN system is implicated in both production and perception of facial emotional expression, one can really expect an alteration of MN in PD, even if the MN network is not the only neuronal system involved in emotion perception (Wang, Larson, Bowen, & van Belle, ).…”
Section: Mirror Neurons and Neurodegenerative Diseasesmentioning
confidence: 55%
“…Overall, fMRI data (Anders et al, ; Pohl et al, ) and neuropsychological studies listed above considerably support the contention that empathy deficits in PD are linked to an impairment of the MN network.…”
Section: Mirror Neurons and Neurodegenerative Diseasesmentioning
confidence: 76%
See 1 more Smart Citation
“…Several studies have demonstrated this is related to the destruction of pigmented neurons in the substantia nigra (Zetterström et al, 1997 ; Kordower et al, 2013 ). Its most frequent symptoms are: tremor, rigidity and bradykinesia, but also cognitive alterations, lack of emotion expressiveness (Pohl et al, 2017 ) and autonomy problems (Fauci et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%